COMPLIANCE IN CORPORATE GOVERNANCE OF PUBLICLY-HELD COMPANIES AND THEIR IMPACT ON PROFITABILITY, RISK, SIZE, GROWTH AND VALUE, AND PERFORMANCE VARIABLES - Mussatto, Alejandro Torres; Mayne, Eric Salinas (European Scientific Journal, ESJ, 2015)
The current rules in the legislation, mandatory for the largest companies in the capital market in Chile, require compliance of at least 19 best practices on corporate governance. The study determines a number of financial variables covering mainly the risk, profitability, valuation, size, growth and projections for those companies belonging to the selective shares of the Santiago stock exchange price index. It aims to measure the variables previously mentioned for analysis, and to determine the differences between companies that meet to a higher extent the standards of best practices of corporate governance and the ones that comply partially. The companies that largely comply with current legislation show better returns compared to those that comply to a lesser extent the standards and the benchmark index. Under this same distinction, those companies that show better compliance carry a total and systematic risk, risk-adjusted, with better performance, size and valuations, as well as factors of growth and projection of the share prices.